Cytogenetic features of human trophoblast cell lines SWAN-71 and 3A-subE. (April 2017) - Reiter, Jill L.; Drendel, Holli M.; Chakraborty, Sujata; Schellinger, Megan M.; Lee, Men-Jean; Mor, Gil
Abstract: Immortalization of primary cells with telomerase is thought to maintain normal phenotypic properties and avoid chromosomal abnormalities and other cancer-associated changes that occur following simian virus 40 tumor antigen (SV40 Tag) induced immortalization. However, we report that the human telomerase reverse transcriptase (hTERT)-immortalized SWAN-71 trophoblast cell line has a near pentaploid 103∼119, XXXX[cp20] karyotype. Additionally, DNA typing analysis indicated that SWAN-71 cells have acquired microsatellite instability. In comparison, the post-crisis SV40-transformed trophoblast cell line 3A-subE was hypertriploid 69∼81, XX[cp20]. Both cell lines contained multiple specific clonal rearrangements. These findings emphasize the need to monitor for genetic instability in hTERT-immortalized cells. Highlights: Human 3A-subE trophoblast cell line has a hypertriploid 69∼81, XX[cp20] karyotype. Human SWAN-71 trophoblast cell line has a pentaploid 103∼119, XXXX[cp20] karyotype. The SWAN-71 DNA profile reveals evidence of microsatellite instability. The hTERT-immortalized SWAN-71 cell line has apparently undergone cellular crisis.